2012
DOI: 10.1074/jbc.m111.299180
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl Hydroxylase-dependent Modulation of Eukaryotic Elongation Factor 2 Activity and Protein Translation under Acute Hypoxia

Abstract: Background: Translational arrest is a classical cellular response to hypoxia, the underlying mechanisms of which are unknown. Results: Inhibitory phosphorylation of eukaryotic elongation factor 2 by acute hypoxia depends on oxygen-sensitive prolyl hydroxylases (PHDs). Conclusion:The elongation phase of protein synthesis is regulated by PHDs. Significance: This work unravels a novel cellular process controlled by PHDs, potential pharmacological targets in several human diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 42 publications
1
25
1
Order By: Relevance
“…1A). Our findings are distinct from those of an earlier study, which reported a rapid increase in eEF2K phosphorylation during hypoxia (17); our data also revealed the existence of a second, slower, and much more marked rise in eEF2 phosphorylation. The rapid changes in eEF2 phosphorylation observed in the previous study likely reflect different regulatory inputs into eEF2 (17).…”
Section: Hypoxia Elicits a Delayed Increased In Eef2 Phosphorylationcontrasting
confidence: 57%
See 1 more Smart Citation
“…1A). Our findings are distinct from those of an earlier study, which reported a rapid increase in eEF2K phosphorylation during hypoxia (17); our data also revealed the existence of a second, slower, and much more marked rise in eEF2 phosphorylation. The rapid changes in eEF2 phosphorylation observed in the previous study likely reflect different regulatory inputs into eEF2 (17).…”
Section: Hypoxia Elicits a Delayed Increased In Eef2 Phosphorylationcontrasting
confidence: 57%
“…The activation of AMPK or inhibition of mTORC1 signaling, each of which can acutely activate eEF2K, likely serves to provide a short-term modulation of eEF2K activity. The long-term adaptive response revealed in this study is distinct from the rapid responses to PHD inhibition reported recently (17).…”
Section: Discussionmentioning
confidence: 40%
“…Their role in HIF-α hydroxylation evolved in animals, possibly via fusion of a basic helix-loop-helix domain transcription factor with an EF-Tu, collagen, or Skp1-related or Skp1-derived substrate. The observation that PHD2 interacts with, but apparently does not hydroxylate, eEF2, the eukaryotic counterpart to prokaryotic EF-G, an EF-Tu homolog (15), is interesting because it may reflect an ancestral relationship between PPHD and EF-Tu. Competition between HIF-α and eEF2 [and potentially other PHD substrates; e.g., pyruvate kinase M2 (38) or centrosomal protein 192 (39)], may help regulate the hypoxic response in higher animals.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia (0.5-1.5% O 2 ) inhibits protein synthesis through suppression of multiple key regulators of eIF2␣, eEF2, p70 S6 , mTOR, and rpS6 (4,(13)(14)(15). Moderate hypoxia (1.5% O 2 ) in combination with serum deprivation effectively inhibits mTOR activity and causes hypophosphorylation of the mTOR substrates 4E-BP1and S6K in normal cells (16).…”
mentioning
confidence: 99%